Dispositional Self-Construal Modulates the Empathy for Others’ Pain: An ERP Study - Chen, Jie; Chang, Bijia; Li, Wenjie; Shi, Yupeng; Shen, Haizhou; Wang, Rong; Liu, Lei (Frontiers in Psychology, 2020)
Previous studies have shown that temporal self-construal priming can modulate the empathic neural responses to others’ pain. However, little is known about the influences of the dispositional self-construal on empathic neural responses to others’ pain. The present study aimed to investigate neural correlates that underlie the modulation effect of dispositional self-construal on perception of others’ pain. Event-related potentials were recorded for pictures depicting the hands of strangers in painful or no-painful situations while subjects performed a pain judgment task. The regression analysis on behavioral data showed that the level of interdependent self-construal could positively predict behavioral ratings of perceived pain, but not the self-unpleasantness. The ERP results showed painful stimuli elicited decreased N2 amplitudes and larger P3 amplitudes than those by no-painful stimuli. Moreover, the level of interdependent self-construal (interdependence minus independence scores) could predict the amplitude differences on the P3 component (painful minus neutral stimulus conditions), but not the N2 component: the higher the level of the interdependent self-construal, the larger amplitude differences of P3 to painful stimuli (v.s. no-painful stimuli). These findings extended previous studies by showing a clear modulation effect of the dispositional self-construal on empathic neural responses to others’ pain, and that this modulation effect occurred at the late cognitive evaluation stage indexed by the P3 component.